2017
DOI: 10.1016/j.jceh.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Brain Microstructural Correlates of Cognitive Dysfunction in Clinically and Biochemically Normal Hepatitis C Virus Infection

Abstract: Our result show that HCV positive individuals would demonstrate structural brain abnormalities and neurocognitive dysfunction as well as the changes in cell component and extracellular space in the white matter regions of brain in asymptomatic HCV infection by using DTT metrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 44 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…The present study is also generally consistent with previous neuroimaging studies demonstrating a range of HCV associated CNS effects (Forton, Allsop et al 2001, Taylor, Letendre et al 2004, Weissenborn, Krause et al 2004, McAndrews, Farcnik et al 2005, Grover, Pavese et al 2012, Bladowska, Zimny et al 2013, Bladowska, Knysz et al 2014, Thames, Castellon et al 2015, Pflugrad, Meyer et al 2016, Kharabian Masouleh, Herzig et al 2017, Kumar, Deep et al 2017), and with the literature on neuroimmune pathways leading to HCV associated neuropsychiatric symptoms and CNS changes. Viruses can cross tight junctions due to high levels of viremia and inflammation, and HCV RNA has been detected in cerebrospinal fluid and brain parenchyma (Laskus, Radkowski et al 2002, Laskus, Radkowski et al 2005, Letendre, Paulino et al 2007, Adinolfi, Nevola et al 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study is also generally consistent with previous neuroimaging studies demonstrating a range of HCV associated CNS effects (Forton, Allsop et al 2001, Taylor, Letendre et al 2004, Weissenborn, Krause et al 2004, McAndrews, Farcnik et al 2005, Grover, Pavese et al 2012, Bladowska, Zimny et al 2013, Bladowska, Knysz et al 2014, Thames, Castellon et al 2015, Pflugrad, Meyer et al 2016, Kharabian Masouleh, Herzig et al 2017, Kumar, Deep et al 2017), and with the literature on neuroimmune pathways leading to HCV associated neuropsychiatric symptoms and CNS changes. Viruses can cross tight junctions due to high levels of viremia and inflammation, and HCV RNA has been detected in cerebrospinal fluid and brain parenchyma (Laskus, Radkowski et al 2002, Laskus, Radkowski et al 2005, Letendre, Paulino et al 2007, Adinolfi, Nevola et al 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, our primary objective was to determine whether, relative to non-infected controls, individuals with HCV exhibit differences in brain activation during a DDT. Previous neuroimaging studies comparing untreated adults with HCV to non-infected controls have found a variety of HCV associated changes using various methods (electroencephalogram (EEG) (Weissenborn, Krause et al 2004); magnetic resonance spectroscopy (MRS) (Forton, Allsop et al 2001, Taylor, Letendre et al 2004, Weissenborn, Krause et al 2004, McAndrews, Farcnik et al 2005, Bladowska, Zimny et al 2013, Thames, Castellon et al 2015); multimodal MRI or diffusion tensor imaging (DTI) (Bladowska, Zimny et al 2013, Thames, Castellon et al 2015, Kharabian Masouleh, Herzig et al 2017, Kumar, Deep et al 2017); perfusion-weighted MRI (Bladowska, Zimny et al 2013, Bladowska, Knysz et al 2014); positron emission tomography (PET) (Grover, Pavese et al 2012, Pflugrad, Meyer et al 2016)). Collectively, findings could be interpreted to suggest that HCV causes or is associated with central nervous system (CNS) inflammation, damage, and/or neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Bladowska et al [56], however, observed a decrease in diffusivity in several white matter tracts in their study. One other study also found significantly decreased fractional anisotropy (an index of microstructural integrity) in asymptomatic HCV positive patients on sensory, inferior longitudinal fascicules and STR fibre bundles compared with uninfected healthy controls [58].…”
Section: Neuroimaging Studiesmentioning
confidence: 86%
“…Reduced cortical thickness in frontal areas with [26] or without [27] occipital involvement Posterior insula and thalamic atrophy [9] Progressive amygdala and parahippocampal atrophy [9] DAA Reduced frontal cortical volumes [28] DTI Increased MD and reduced FA in global WM [15] more evident in fronto-temporal areas [29] and body of CC [9,24,30] Increased MD in external capsule [4] and fronto-occipital fasciculus [4,9,24] Decreased FA in bilateral middle cerebellar peduncles [24] and superior thalamic radiation [31] Increased FA in the basal ganglia [4] DAA Increased FA in association, commissural and projection tracts [25] Decreased MD in association and projection tract [25] fMRI Altered cortical connectivity possibly due to frontal deficit [32,33] IFN-α Reduced ventral striatum activation [22] and global network efficiency [34] MRS Decreased NAA in anterior [35][36][37] and posterior WM [4,37] Normal [18,35,[37][38][39][40][41][42] or decreased NAA in cortical GM [43] Increased Cho in frontal [35,37,38,43,44] and posterior WM…”
Section: Structural Imagingmentioning
confidence: 99%
“…In HCV-infected subjects, reduced local complexity with increased anisotropy is observed in the basal ganglia, correlating mainly with semantic fluency, and in the bilateral thalami [4]. Thalamic efferents, as the superior thalamic radiation, also show structural alterations that correlate with impairment on tests of attention and executive functions [31].…”
Section: Diffusion Tensor Imaging (Dti)mentioning
confidence: 99%